2012
DOI: 10.1111/j.1440-1746.2012.07068.x
|View full text |Cite
|
Sign up to set email alerts
|

Narrow‐band imaging on screening of esophageal lesions using an ultrathin transnasal endoscopy

Abstract: Background and Aim: Ultrathin transnasal endoscopy, used extensively in Japan, is considered to have inferior image quality and suction performance, and questionable diagnostic performance. So the aim of the present study was to compare the diagnostic performance of white light (WL) examination and non-magnified narrow-band imaging (NBI) examination in screening for esophageal disorders with ultrathin transnasal endoscopy. Methods: A prospective case study of 105 consecutive patients screened for upper gastroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…One study evaluated the methods in patients who already had a diagnosis of pre-malignant lesions or squamous cell carcinoma of the esophagus [31]. The other study evaluated the methods in the general population [27]. …”
Section: Resultsmentioning
confidence: 99%
“…One study evaluated the methods in patients who already had a diagnosis of pre-malignant lesions or squamous cell carcinoma of the esophagus [31]. The other study evaluated the methods in the general population [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Multiple prospective studies have shown that nonmagnified NBI examination is superior to WLI in detection of early esophageal lesions for screening of high-risk patients (10)(11)(12)(13) (15). In addition, NBI endoscopy also had a higher specificity comparing to Lugol chromoendoscopy (per lesion analysis 82% vs. 37%).…”
Section: Review Articlementioning
confidence: 99%
“…In contrast, excellent detection rates for oesophageal and gastric cancers have previously been reported when using UT endoscopy in combination with chromoendoscopy using indigo carmine and iodine 64. It has also been suggested that if image enhancing techniques such as NBI (or FICE) can be applied through a UT endoscope, this may be useful in improving the detection of oesophageal premalignant lesions 65. This is now possible with the latest series of UT scopes.…”
Section: Gastric Cancermentioning
confidence: 99%